Development of Video Tutorial Operating CNC Machine Using Nanjing Swansoft Simulator Based on YouTube Chanel as an Alternative Media on Network Learning - Muslim, Muslim; Basuki, Nur; Riadi, Selamat (Universitas Negeri Medan, 2022)
This study examines the limitations of CNC (Computer Numerical Control) machine facilities owned by the Department of Mechanical Engineering Education, Faculty of Engineering, State University of Medan (JPTM FT UNIMED) which are obstacles for students in improving competence. From these problems, alternatives and solutions are needed, namely, utilizing the Nanjing Swansoft simulator software to improve the competence of CNC machining techniques. The lack of CNC machine facilities used in learning CNC machining engineering courses at JPTM FT UNIMED so research on this problem is still needed. This study aims to produce a video tutorial on how to operate a CNC machine using a Nanjing Swansoft simulator based on a YouTube channel. This study aims to produce a video tutorial on how to operate a CNC machine using a nanjing swansoft simulator based on a YouTube channel. The type of research used is research and development (Research and Development) from Borg and Gall. The feasibility of the product was carried out by validating media experts, material experts, learning design experts, small group tests, and field trials for students of JPTM FT UNIMED. Based on the results of product validation, the percentage of media expert assessment results is 92%, a material expert is 91%, and a learning design expert is 92%. Student responses in small group trials obtained a percentage of 92% and 93% in field trials. Based on these results, it can be concluded that the CNC Practice Video Tutorial Using the Nanjing Swansoft Simulator Based on the YouTube Channel that has been developed is feasible to be used as an alternative media for online learning for students of the Department of Mechanical Engineering Education, Faculty of Engineering, State University of Medan.